Semiotic Analysis of the Function of Chaos in Logos in the First Chapter of Saadi's Gulistan - Shirzad Tayefi; Zohreh Sohrabi (مطالعات زبانی و بلاغی)
Gulistan, as a literary text reflecting various cultural issues from aesthetics to politics and religion, is an appropriate ground for the semiotic analysis of Saadi's meaning-making strategies to express these issues. The present paper with a descriptive-analytical method and based on library research seeks to meet this goal by examining Gulistan's first chapter through Juri Lotman's cultural semiotic approach and Klinkenberg's ideas about semiotic insecurity. Golistan's first chapter, representing the relationship between the king and his inferiors, focuses on the contrasts between Dervish and other social strata. This, as the major binary opposition through which Saadi expresses different cultural issues, has a close connection with the concepts of chaos and logos in semiotics analysis of which can help us find Saadi's major strategies to meaning-making. The opposition of chaos and logos is itself embedded in semiotic insecurity as an inseparable part of the discourse of power. The relationship between the king and his inferiors as a power relation mostly represents a breakdown of the political order which indicates that the domain of logos is plunged into chaos in two different ways. In the domain of logos depicted within the space of stories, the chaos caused by the inferiors dominates the political domain of order; however, it is subdued in the domain of logos outside of the space of the stories. This is while the chaos caused by Dervish, as a representative of a social stratum with a special discourse of its own, disturbs the domain of logos both inside and outside of the space of the stories. However, if the concept of power is defined as wider than the political power, Dervish's behavior does not disturb the domain of logos outside of the stories, nor is it regarded as chaos within the stories.